Evaluation of photosynthesis, physiological, and biochemical responses of chickpea (Cicer arietinum L. cv. Pirouz) under water deficit stress and use of vermicompost fertilizer - Saeed Reza Hosseinzadeh; Hamzeh Amiri; Ahmad Ismaili (Journal of Integrative Agriculture, 2018)
One goal in the face of drought stress conditions is to increase growth and yield through the reduction of negative effects of stress. Vermicompost can play an effective role in plant growth and development and in reducing harmful effects of various environmental stresses on plants due to its porous structure, high water storage capacity, having hormone-like substances, plant growth regulators, and high levels of macro and micro nutrients. This study considered the physiological, biochemical, and photosynthetic responses of the chickpea to different combinations of vermicompost and water stress in a greenhouse environment. Two factors were involved, addition of vermicompost to soil at four ratios: control (100 wt% (weight percentage) soil); 10 wt% vermicompost+90% soil; 20 wt% vermicompost+80 wt% soil; 30 wt% vermicompost+70 wt% soil weight percentage, and treatment of water stress at three levels including 75, 50, and 25% of field capacity. The results showed that vermicompost had a significant effect on all traits under stress and non-stress conditions. Application of vermicompost in soil, especially at the levels of 20 and 30 wt% significantly increased all studied traits under non-stress conditions. Under moderate stress conditions, vermicompost at 30 wt% treatment resulted in a significant increase in the photosynthetic pigments, CO2 assimilation rate, internal leaf CO2 concentration, transpiration, the maximal quantum yield of photosystem II (PSII) photochemistry (Fv/Fm), concentrations of Ca and K in root and leaf tissues, proline and soluble protein contents in root tissues. Peroxidase (POX) and catalase (CAT) enzyme activities decreased significantly with increasing proportions of vermicompost, but the activity of superoxide dismutase was not significantly different. In conclusion, the above results showed that vermicompost fertilizer had a positive effect on physiological, biochemical, and photosynthetic responses of chickpea under non-stress and moderate stress conditions, but no positive effect was determined under severe water stress.